2015
DOI: 10.1186/s40200-016-0230-1
|View full text |Cite
|
Sign up to set email alerts
|

Does this patient have pheochromocytoma? A systematic review of clinical signs and symptoms

Abstract: ContextPheochromocytoma is a rare disease but with high mortality if it is not being diagnosed early. Several biochemical tests with high accuracy have been obtained, but the clinical threshold for request of these tests is not determined clearly.ObjectivesTo determine the Likelihood Ratios of clinical symptoms and signs in diagnosing pheochromocytoma. And also meta-analysis of their sensitivity in this disease.Data sourcesMEDLINE was searched for relevant English-language articles dated 1960 to February 2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…Less frequently, PPGL may manifest as nausea, vomiting, flushing, and weight loss. Recently, Pourian et al established a clinical symptomatology likelihood ratio, which found that only palpitations, headache, and diaphoresis are significant when considering a possible PPGL diagnosis (5). Although the general symptoms remain nonspecific, catecholamine-induced organ damage, particularly to the endocrine, metabolic, and cardiovascular systems should indicate a full diagnostic workup for PPGL.…”
Section: Introductionmentioning
confidence: 99%
“…Less frequently, PPGL may manifest as nausea, vomiting, flushing, and weight loss. Recently, Pourian et al established a clinical symptomatology likelihood ratio, which found that only palpitations, headache, and diaphoresis are significant when considering a possible PPGL diagnosis (5). Although the general symptoms remain nonspecific, catecholamine-induced organ damage, particularly to the endocrine, metabolic, and cardiovascular systems should indicate a full diagnostic workup for PPGL.…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the unique nature of paroxysmal hypertension in pheochromocytoma and the fact that blood pressure can be entirely normal in the inter crisis period. 5 While orthostatic hypotension is well described in pheochromocytoma with a sensitivity varying from 21-50%, this patient had orthostatic hypertension. Orthostatic hypertension is an underappreciated clinical sign, owing to lack of knowledge among physicians and varying definitions.…”
Section: Discussionmentioning
confidence: 74%
“…Orthostatic hypertension is an underappreciated clinical sign, owing to lack of knowledge among physicians and varying definitions. 5 The magnitude of increase in sphygmomanometric pressure required for a diagnosis of orthostatic hypertension is an increase in systolic BP of 20 mmHg or more with no defined change in diastolic blood pressure. Pheochromocytoma is cited as a reason for the same.…”
Section: Discussionmentioning
confidence: 99%
“…Classically they present with the triad of headache, palpitations and hypertension (sustained or paroxysmal) [ 84 ]. However a wide range of presentations have been described, with some patients presenting due to complications of catecholamine excess (cardiac complications, stroke, diabetes mellitus) whilst others are diagnosed following the incidental finding of an adrenal mass on imaging for other reasons [ 85 ]. Non-secretory PPGLs are often discovered incidentally, for example patients may present with a lump in the neck.…”
Section: The Patient With Phaeochromocytoma/paraganglioma (Ppgl)mentioning
confidence: 99%